Political instability: A major challenge for nation building in the context of Nepal - Guragain , Govinda Prasad (Medha: A Multidisciplinary Journal, 2023)
This article explores the difficulties associated with nation-building in Nepal, illuminating the country’s diverse cultural, ethnic, religious, and linguistic landscape. Conflicts can arise from differences in identity and perspective, and this diversity frequently acts as a fertile ground for them. These disputes can take many different forms, from tensions within the socioeconomic class to movements calling for independence or even division between various racial or cultural groups. These disputes have their roots in antiquity and are intricately linked to the development of human societies. In Nepal, these tensions are made worse by large differences in income, opportunities, and resource availability, which pose serious obstacles to the country’s development and attempts to foster unity. The idea that effectively managing these conflicts and inequalities is essential to Nepal’s nation-building efforts is central to the article’s narrative. The goal is to integrate diverse communities into nation-building efforts and ensure their meaningful involvement in determining the course of the nation by addressing the root causes of these disparities and promoting inclusive governance and dialogue. While not exclusive to Nepal, this focus on diversity and conflict resolution is a reflection of the difficulties encountered by many countries attempting to manage diversity in the modern world.